The Government Financial Performance Provincial Regions in Indonesia: The Effect of Capital Expenditure, Remaining Budget Financing, and Prosperity Rate - Azzahra, Avina; Rita Martini; Bainil Yulina (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to investigate the impact of capital spending, remaining budget financing and prosperity level on the financial performance of Provincial Governments in Indonesia. This particular research style serves is a quantitative research using secondary data obtained from the official website of bpk.go.id. The population in this study is 38 provinces in Indonesia with a total sample of 34. The sampling method in this study uses Nonprobability Sampling with purposive sampling technique. The hypothesis test of this study used multiple linear regression analysis with the help of softwarwe EViews 12. The results of this study show that partially capital expenditure and remaining budget financing have a negative and significant effect on financial performance. Furthermore, the prosperity level has no effect on financial performance. the simultaneous test stated that capital expenditure, remaining budget financing, and prosperity level together had a significant effect on the financial performance of Provincial Governments in Indonesia.